Paradigma Pelindungan Anak Berbasis Sistem - Susanto, Susanto (Jurnal Aspirasi, 2017)
Every child has the right to be able to live, grow, develop, and participate fairly according to human dignity, and to be protected from violence and discrimination, but the fact is that condition of Indonesian children is still far from the ideal. There are still many Indonesian children who have not received protection from violence and discrimination, and they aften experience bad and treatment the on going, violence, poor up bringing and neglect. Taking this in to account, this paper attempts to answer two things, first, and often they implementation of child protection so far, second, the best system based formula for child protection that should be use. Using a literacy study approach, this review concludeds. That child protection policy in Indonesia until now still contains various weaknesses. This is reflected in the lack of existing norms in legislation, sectoral and non-integrated policies, fragmented and unfocused budgets, weak institutional coordination, poor handling of child protection for its case fased approach and forgetting long-term solutions, and misperceptions on the functions -child protection Institutions. Such challenges need to be resolved with a system-based policy. This approach necessitates the completion of various policies for the implementation of child protection. Both at the level of legislation and on the implementation. It is also necessary to strengthen child protection institution in Indonesia both in terms of human resources and of the budget that sustains it.Setiap anak berhak untuk dapat hidup, tumbuh, berkembang, dan berpartisipasi secara wajar sesuai dengan harkat dan martabat kemanusiaan, serta mendapat pelindungan dari kekerasan dan diskriminasi, namun pada kenyataannya kondisi anak di Indonesia masih jauh dari harapan ideal itu. Masih banyak anak Indonesia yang belum memperoleh pelindungan dari kekerasan dan diskriminasi, bahkan tidak jarang anak yang mengalami perlakuan buruk, kekerasan, salah asuh dan penelantaran. Berangkat dari keprihatinan itu, tulisan ini berupaya menjawab dua hal, pertama, bagaimana penyelenggaraan pelindungan anak selama ini, kedua, bagaimana formula pelindungan anak dengan sistem sebaiknya dilakukan. Dengan menggunakan pendekatan studi literartur, kajian ini menyimpulkan, bahwa kebijakan pelindungan anak di Indonesia sampai saat ini masih mengandung berbagai kelemahan. Hal itu tampak pada lemahnya norma yang ada dalam peraturan perundangan, kebijakan yang bersifat sektoral dan tidak padu, anggaran yang terpecah-pecah dan tidak fokus, lemah koordinasi antarlembaga, penanganan pelindungan anak bersifat kasuistik dan melupakan penyelesaian jangka panjang, dan salah persepsi terhadap fungsi lembaga-lembaga pelindungan anak. Kondusi pelindungan anak di Indonesia yang demikian perlu diselesaikan dengan kebijakan pelindungan berbasis sistem. Pendekatan ini meniscayakan penyempurnaan berbagai kebijakan penyelenggaraan pelindungan anak. Baik pada level peraturan perundangan maupun pada pelaksaan. Selain itu juga perlu dilakukan penguatan kelembagaan pelindungan anak di Indonesia baik dari sisi sumber daya manusia maupun dari anggaran yang menopangnya.